Investigation of the biological and photophysicochemical properties of new non-peripheral fluorinated phthalocyanines - Celik, Cetin; Farajzadeh, Nazli; Akin, Mustafa; Atmaca, Goknur Yasa; Saglam, Ozgul; Saki, Neslihan; Erdogmus, Ali; Kocak, Makbule Burkut (ROYAL SOC CHEMISTRY, 2021)
This study presents the synthesis of a series of new tetra-substituted phthalocyanines bearing 3,5-bis(trifluoromethyl)phenoxy groups at non-peripheral positions. The resulting macromolecules were characterized by performing different spectroscopic methods including H-1 NMR, UV-Vis, FT-IR, and mass spectroscopy. In this study, the synergistic effect of phthalocyanines used as colorants in ink formulas with other chemicals available was probed for the first time. The synergistic effect of methyl laurate on the biological and antioxidant activities of the compounds (2-5) was investigated. Moreover, the therapeutic properties of the complexes (3, 6, and 7) were investigated using photochemical methods. Upon comparison, complex 7 (phi(Delta) = 0.42) was found to be more effective than complex 6 (phi(Delta) = 0.40) and complex 3 (phi(Delta) = 0.27) in terms of producing singlet oxygen. The results confirmed that the heavy atom effect improves the therapeutic effects.
Keywords: Chemistry